The cognitive behavioral therapy causes an improvement in quality of life in patients with chronic musculoskeletal pain - Martha M. C. Castro; Carla Daltro; Durval Campos Kraychete; Josiane Lopes (Arquivos de Neuro-Psiquiatria)
Chronic pain causes functional incapacity and compromises an individual's affective, social, and economic life. OBJECTIVE: To study the cognitive behavioral therapy (CBT) effectiveness in a group of patients with chronic pain. METHODS: A randomized clinical trial with two parallel groups comprising 93 patients with chronic pain was carried out. Forty-eight patients were submitted to CBT and 45 continued the standard treatment. The visual analogue, hospital anxiety and depression, and quality of life SF-36 scales were applied. Patients were evaluated before and after ten weeks of treatment. RESULTS: When the Control Group and CBT were compared, the latter presented reduction of depressive symptoms (p=0.031) and improvement in the domains 'physical limitations' (p=0.012), 'general state of health' (p=0.045), and 'limitations by emotional aspects' (p=0.025). CONCLUSIONS: The CBT was effective and it has caused an improvement in more domains of quality of life when compared to the Control Group, after ten weeks of treatment.